Semiconductor/polymer electroylte junction solar cell - Mohamad, Souad A.; AROF, A.K; ALI,, M.H. (2007)
Semiconductor - solid polymer electrolyte junction can also be used for conversion of light energy into electricity apart from the conventional semiconductor n-p junctions [1]. In semiconductor - electrolyte junction, a charge transfer from the electrode to the electrolyte has to take place to enable current to flow through an external circuit. The use of semiconductor-liquid electrolyte junction was first suggested by Fujishima and Honda [2] and Gerischer [3]. Unfortunately, there are problems in the use of liquid electrolytes such as difficulty in handling, electrochemical corrosion, encapsulation, and portability. Some of these problems can be addressed using a ‘solid polymer electrolyte’.